A Review on Controlling of Julia and Mandelbrot Sets - Ankit Mundra, Anju Yadav, Mamta Rani, Vivek K Verma (International Journal of Advanced Science and Technology, 2019)
Julia and Mandelbrot sets have been intensively studied, but most of the studies are limited to its properties and drawings of its graphics for different types of functions. So, the effective control over the Julia and Mandelbrot sets is an active research area. In this paper, we have given a detailed review on controlling of Julia and Mandelbrot sets by different methods.